2022
DOI: 10.1371/journal.pone.0267195
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the pulmonary mycobiome in subjects with and without chronic obstructive pulmonary disease

Abstract: Background Few studies have examined the stability of the pulmonary mycobiome. We report longitudinal changes in the oral and pulmonary mycobiome of participants with and without COPD in a large-scale bronchoscopy study (MicroCOPD). Methods Repeated sampling was performed in 30 participants with and 21 without COPD. We collected an oral wash (OW) and a bronchoalveolar lavage (BAL) sample from each participant at two time points. The internal transcribed spacer 1 region of the ribosomal RNA gene cluster was P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…The airway mycobiome in COPD is characterised by specific fungal genera, Aspergillus , Curvularia and Penicillium , which were associated with exacerbations and increased mortality [ 18 ]. A longitudinal study demonstrated that the pulmonary mycobiome was less stable than the oral mycobiome, and neither COPD diagnosis nor intercurrent antibiotic use seemed to influence stability [ 19 ].…”
Section: Pulmonary Mycobiota and Chronic Respiratory Infectionsmentioning
confidence: 99%
“…The airway mycobiome in COPD is characterised by specific fungal genera, Aspergillus , Curvularia and Penicillium , which were associated with exacerbations and increased mortality [ 18 ]. A longitudinal study demonstrated that the pulmonary mycobiome was less stable than the oral mycobiome, and neither COPD diagnosis nor intercurrent antibiotic use seemed to influence stability [ 19 ].…”
Section: Pulmonary Mycobiota and Chronic Respiratory Infectionsmentioning
confidence: 99%